Greeks and partial differential equations for some pricing currency options models - Shokrollahi, Foad; Kilicman, Adem; Ibrahim, Noor Akma; Ismail, Fudziah (Institute for Mathematical Research, Universiti Putra Malaysia, 2015)
In this study, we consider some pricing currency options models, which are using the Brownian motion, the fractional Broanian motion and the mixed fractional Brownian motion. The partial differential equations for values of European currency options and some Greeks are obtained for all these models. In addition, in the fractional environment, that parameter H has huge effect on pricing options, the impact of the Hurst parameter H is presented. Besides, comparing the Greeks for three currency options models are illustrated by some figures.